2008
DOI: 10.1002/dvdy.21459
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparative expression of zebrafish calpain system genes during early development

Abstract: The classic calpain system has been implicated in regulating a variety of cellular processes including cell adhesion, migration, and intracellular signaling; however, little is known regarding the function of this system in vivo. Two heterodimeric Ca 2؉ -dependent cysteine proteases, -calpain (CAPN1) and m-calpain (CAPN2), and the endogenous inhibitor calpastatin (CAST) comprise the classic/ubiquitous calpain system in mammals. Recently, knockout of two murine classic calpain genes, Capn2 and Capn4/Capns1, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…The phylogenetic tree was constructed by the neighbor-joining (NJ) method using the programs CLUSTAL X1.83 (Lepage and Bruce, 2008) and MEGA4 (Tamura et al, 2007). The conserved domain of the C. carpio CAST protein was analyzed using the NCBI CD-Search tool, and the secondary structure was predicted using GOR IV (http://gor.bb.iastate.…”
Section: Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogenetic tree was constructed by the neighbor-joining (NJ) method using the programs CLUSTAL X1.83 (Lepage and Bruce, 2008) and MEGA4 (Tamura et al, 2007). The conserved domain of the C. carpio CAST protein was analyzed using the NCBI CD-Search tool, and the secondary structure was predicted using GOR IV (http://gor.bb.iastate.…”
Section: Sequence Analysismentioning
confidence: 99%
“…In chicken, CAST expression may be related to muscle fiber development (Zhang et al, 2012). Lepage and Bruce (2008) reported the characterization and comparative expression of calpain in zebrafish. Overturf and Gaylord (2009) compared the expression of the CAST gene in the muscle of fish fed fishmeal with plant protein diets and suggested that diets replacing fishmeal with plant material can have some effects on protein turnover in the muscle of rainbow trout.…”
Section: Introductionmentioning
confidence: 99%
“…Fish due to polyploidization events in nature history have a duplicate set of most of the fifteen mammalian calpains and calpain-related molecules (Lepage & Bruce, 2008;Macqueen et al, 2010).…”
Section: Calpain-calpastatin System In Vertebratesmentioning
confidence: 99%
“…-dependent cysteine proteinases implicated with pro-and anti-apoptotic functions in mammals [75]. So far, it has been documented that calpains and the related regulatory protein calpastatin are differentially expressed in starving trout [76,77], in developing zebrafish [78], and in trout hepatocytes exposed to anoxia in vitro [79], where an increase in calpain activity might facilitate apoptosis by cleavage of anti-apoptotic proteins [80].…”
Section: Other Executioners and Regulators Of Apoptosismentioning
confidence: 99%